1-A-D-19. Decoding information of visual perception of body parts. Issue 6 (June 2015) - Nakamura, Misaki; Yanagisawa, Takufumi; Okamura, Yumiko; Nakagiri, Yumiko; Hirata, Masayuki; Araki, Toshihiko; Okamoto, Yuna; Onishi, Mai; Yorifuji, Shiro
<x xml:space="preserve">Abstract</x> We recognize body parts in categories. Previous studies have shown that event-related magnetic fields (ERF) called M190 are evoked by perceptions of the human body, either as a whole or in part. This response occurs approximately 190 ms after visualization of body images. However, it is not revealed how M190 involves categorical perceptions of body parts. We evaluated the M190 responses using a decoding method to quantify body information categories. Nine subjects underwent measurements of brain activities with magnetoencephalography (MEG) while viewing 14 images of feet, hands, mouths, and objects. We decoded categories of the presented images from the MEG signal using a support vector machine (SVM) and calculated accuracy by 10-fold cross-validation. For each subject, the response that seemed to be M190 was observed. By using the signals estimated in the occipitotemporal cortex (p < 0.01, Student's t-test), MEG signals corresponding to three types of body categories were classified with significantly higher accuracy (with a peak at 48%) compared with those corresponding to randomized categories. According to the time course and location, these responses involving categorical classifications were suggested to be M190. Therefore, M190 is suggested to include information regarding body part categories.